The Effect of Inoculum Type and Mycorrhiza Dosage on Growth and Production of Mung Bean Vigna Radiata L. - Syamsuddin Djauhari; Jami'at Dwi Elriyono; Bambang Tri Rahardjo (University of Brawijaya, 2021)
Mung bean (Vigna radiata L.) is the third most essential legume crop commodity after soybeans and peanuts. Mung bean production faced problems of nutrient-poor land and soil texture that does not support soybean growth. The solution to overcome these obstacles is the application of mycorrhizae in nutrient-poor soils. This study aimed to determine the effect of various inoculums and mycorrhizal doses on growth and production in mung beans. This study used a Completely Randomized Design with nine treatments and three replications. The research included mycorrhizal inoculation with various treatments, as well as observations with variable plant height, plant biomass, number of pods, wet weight and dry weight of pods, the weight of 50 wet and dry seeds, mycorrhizal infection in roots, and number of spores in 100 gr of soil. The data were analyzed by SPSS 15.0 program for ANOVA. The results indicated that granular (30 gr) had the highest plant height of (41.33 cm), crown weight (30.69 gr), number of pods, wet and dry pod weight is 13.66, 9.84 gr, and 8.86 gr, respectively, 50 kg of wet and dry weight (3.82 and 3.20) and the highest effect on the number of spores at 29.33. The 30 gr tablets treatment showed the highest results on root weight (22.98 gr), while the 30 gr mixture showed the highest results on the percentage of infection (73.33%).